Enzymatic Saccharification and Ethanol Production of Xylem from Purwodadi Botanical Garden Trees - Mariko Sakata; Mito Tokue; Rumi Kaida; Teruaki Taji; Yoichi Sakata; Takahisa Hayashi; Dwi Narko; Fitria Fitria; Danang Sudarwoko Adi; Wahyu Dwianto (Wood Research Journal, 2012)
Recent studies have revealed that sengon (Paraserianthes falcataria) xylem consists of soft walls which are easily hydrolysable with a commercial cellulase preparation. We felt it important to determine the saccharification levels for fast-growing tropical trees, of which sengon, one of the fastest growing tree species in Indonesia, was used as the control wood species. The aim of this study was to screen and evaluate the xylem of Purwodadi Botanical Garden trees for saccharification in order to assess their potential usefulness in bioethanol production. Saccharification and fermentation were first examined in the xylem derived from the branches of 32 trees. The xylem was then milled into powder using a ball mill, and the powdered xylem was digested with a commercial cellulase preparation (Accelerase, Palo Alto, USA) derived from Trichoderma viride. The levels of enzymatic hydrolysis of cellulose and ethanol production were higher for Firmiana malayana and Pterocarpus indicus than for sengon.